2001
DOI: 10.4049/jimmunol.166.7.4570
|View full text |Cite
|
Sign up to set email alerts
|

Novel Androgen-Dependent Promoters Direct Expression of the C4b-Binding Protein α-Chain Gene in Epididymis

Abstract: C4b-binding protein (C4BP) is a large plasma protein composed of seven α-chains and one β-chain and is involved in the fluid phase regulation of the classical pathway of the complement system. Complement inhibitory activity is located in the α-chain, and its mRNA has been detected only in liver to date. Here, we have isolated cDNA clones encoding the α-chain of guinea pig C4BP (C4BPα) and have demonstrated significant C4BPα mRNA expression in epididymis as well as liver. The level of C4BPα transcripts increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…Interestingly, in the rodent animals studied, the expression of CD46 was limited only in testis, indicating that the major function of CD46 among different species lies in fertilization. Moreover, in rodent animals, distribution of complement regulators such as transmembrane type CD55 (decay accelerating factor [DAF]), CD59b, and C4b-binding protein were preferentially expressed in reproductive organs (4,25,30,37,42). In humans, CD46 is expressed on the membrane of all kinds of nucleated cells.…”
mentioning
confidence: 99%
“…Interestingly, in the rodent animals studied, the expression of CD46 was limited only in testis, indicating that the major function of CD46 among different species lies in fertilization. Moreover, in rodent animals, distribution of complement regulators such as transmembrane type CD55 (decay accelerating factor [DAF]), CD59b, and C4b-binding protein were preferentially expressed in reproductive organs (4,25,30,37,42). In humans, CD46 is expressed on the membrane of all kinds of nucleated cells.…”
mentioning
confidence: 99%
“…In the previous report [16], we also demonstrated that murine epididymis express, in an androgen-dependent manner, the transcripts that hybridize with C4BP␣ cDNA. In the present report, we confirmed that these species are transcribed from the C4bpa gene and detected the protein in the epididymis by Western blot analysis and immunohistochemistry.…”
Section: Introductionmentioning
confidence: 58%
“…However, this site was not detected in our experiments. Although further analyses are necessary, Lt is more likely to be a transcription start site, because Lt is located downstream of a hepatocyte nuclear factor-1 (HNF-1) response element and is in a comparable position with the major transcription start site of the human (position ϩ11) [39], guinea pig (position ϩ2) [16], and rat (position Ϫ9) [40] C4BP␣ genes.…”
Section: Analysis Of the Promoter Regionmentioning
confidence: 99%
See 2 more Smart Citations